Nano-structural elucidation in carbon black loaded NR vulcanizate by 3D-TEM and in situ WAXD measurements - Yuko Ikeda (2018)
Three dimensional (3D) visualization of nanometer structure of carbon black dispersion in rubbery matrix has successfully been studied and reported in this paper. Use of 3D-TEM, which is computerized tomography combined with transmission electron microscopy (TEM), enabled us to reconstruct 3D images of carbon black aggregates in natural rubber (NR) matrix. The TEM measurements were conducted by a bright-field method on thin samples without any electron staining. The sample was subject to uni-axial tilting (+65 degree to -65 degree with 2 degree increment) in the sample chamber, and 66 TEM images were taken on each sample. These TEM images were used for computerized tomography to reconstruct the 3D image. This technique is designated as 3D-TEM. The nano-structural features observed by 3D-TEM were in conformity with the electron-conductivity results, and the percolation behavior was recognized. These results were further supplemented by in situ wide-angle X-ray diffraction (WAXD), i.e., simultaneous WAXD and tensile measurements on the sample to observe the strain-induced crystallization in NR vulcanizate. Upon tensile elongation, the crystallization was clearly observed in WAXD in the presence of carbon black, and it contributed to the tensile properties. In order to understand the performances of filled NR vulcanizates, it surely is necessary to know the structural states of the mixed nano-filler and the crystallites produced upon elongation.